Skip to main content
Solve for x
Tick mark Image
Solve for x (complex solution)
Tick mark Image
Solve for y (complex solution)
Tick mark Image
Solve for y
Tick mark Image

Similar Problems from Web Search

Share

\sqrt{x-2}+\left(y+3\right)^{2}-\left(y+3\right)^{2}=-\left(y+3\right)^{2}
Subtract \left(y+3\right)^{2} from both sides of the equation.
\sqrt{x-2}=-\left(y+3\right)^{2}
Subtracting \left(y+3\right)^{2} from itself leaves 0.
x-2=\left(y+3\right)^{4}
Square both sides of the equation.
x-2-\left(-2\right)=\left(y+3\right)^{4}-\left(-2\right)
Add 2 to both sides of the equation.
x=\left(y+3\right)^{4}-\left(-2\right)
Subtracting -2 from itself leaves 0.
x=\left(y+3\right)^{4}+2
Subtract -2 from \left(y+3\right)^{4}.